(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
This contribution aims at exploring Sophia Loren’s “star persona” in the years between 1951, when the actress signs her first contract with Carlo Ponti, and 1968, when she has her first baby with the producer, who she had married in 1957 by proxy in Messico. By examining the roles she embodies on the big screen as well as her public image, I will try to unfold Loren’s complex star image, where the recurring motifs – narrative as well as iconographic – of the siren, Cinderella and Pygmalion are interwoven to a multifaceted idea of femininity, uncertain between tradition and transgression.